South Africa : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2013)
This 2013 Article IV Consultation highlights that South Africa's economy has underperformed other emerging markets and commodity exporters, exacerbating South Africa's already-high levels of unemployment (25 percent) and inequality, and contributing to rising social tensions. At the same time, weak trading partner growth, coupled with declining competitiveness and countercyclical fiscal policy, have led to rising fiscal and current account deficits and made South Africa vulnerable to a prolonged reversal of capital inflows. The outlook is for continued sluggish growth and elevated current account deficits. Growth is projected at 2 percent in 2013 as weak consumption growth and lackluster private investment offset robust public investment and higher export growth.